Mastering the market intelligence challenge - Chari, Murali D. R.; Luce, Kimberlee; Thukral, Inder (MIT Sloan Management Review, 2016)
To thrive in rapidly changing economies in regions such as Asia and Africa, multinationals need to take new approaches to gathering and using marketing intelligence.